Current Perspectives on Viable but Non-Culturable (VBNC) Pathogenic Bacteria - Ramamurthy, Thandavarayan; Ghosh, Amit; Pazhani, Gururaja P.; Shinoda, Sumio (Frontiers in Public Health, 2014)
Under stress conditions, many species of bacteria enter into starvation mode of metabolism or a physiologically viable but non-culturable (VBNC) state. Several human pathogenic bacteria have been reported to enter into the VBNC state under these conditions. The pathogenic VBNC bacteria cannot be grown using conventional culture media, although they continue to retain their viability and express their virulence. Though there have been debates on the VBNC concept in the past, several molecular studies have shown that not only VBNC state can be induced under in vitro conditions but also that resuscitation from this state is possible under appropriate conditions. The most notable advance in resuscitating VBNC bacteria is the discovery of resuscitation-promoting factor (Rpf), which is a bacterial cytokines found in both Gram-positive and Gram-negative organisms. VBNC state is a survival strategy adopted by the bacteria, which has important implication in several fields, including environmental monitoring, food technology and infectious disease management and hence it is important to investigate the association of bacterial pathogens under VBNC state and the water/foodborne outbreaks. In this review, we describe various aspects of VBNC bacteria, which include their proteomic and genetic profiles under the VBNC state, conditions of resuscitation, methods of detection, antibiotic resistance and observations on Rpf.